C1−C2 Arthrodesis With C1 Lateral Mass and C2 Parsicle Screws Combined With Interlaminar Arthrodesis and Wiring. Issue 2 (March 2022) - Rasouli, Jonathan J.; Momin, Arbaz; Fiani, Brian; Shao, Jianning; Moore, Timothy A.
Abstract : C1−C2 arthrodesis is a common procedure performed for the correction of atlantoaxial instability due to a host of pathologies, including degenerative, neoplastic, congenital, and trauma. While there is clinical equipoise, C1−C2 fusion is associated with a lower morbidity than occipital-cervical fusion. However, due to the unique morphometric characteristics of the C1 lateral mass, and the challenges that its fixation presents, some surgeons may elect to extend the construct to the occiput rather than attempt a C1−C2 fusion. Here, we describe our freehand technique of safely and expeditiously performing a C1−C2 fusion with C1 lateral mass and C2 "parsicle" screws. In patients with high preprocedural probability to develop pseudarthrosis, we combine our instrumented fusion with interlaminar bone graft wiring, as similarly described by Gallie. We believe the C2 "parsicle" screw avoids the technical challenges of placing a traditional C2 pedicle screw and accommodates a much larger screw length than those placed in the C2 pars. Practical surgical tips, pearls, and potential complications are discussed in detail.